Exchange of needs and support between unemployed young adults and their parents - Ramirez, Carl Milagros L.
This study seeks to provide an understanding of the exchange of the needs and support between unemployed young adults and their parents from the perspective of young adults. Through a purposive sampling and snowball method, a total of 31 unemployed young adults participated in the focus group discussions and answered survey questionnaires. Results showed that the unemployed young adults' needs were basic needs, emotional needs, financial needs, spiritual or moral needs, social needs and employment. Personal care and entertainment and leisure were also mentioned and is exclusive to this study. On the other hand, parental support obtained included food, shelter, clothing, allowances and money requested by the young adult, advice, words of encouragement, and support in seeking employment. In the activities done by young adults in exchange for their parents support were being thrifty, affectionate, looking for work, doing household chores, running errands, and giving gifts and giving money. The study sheds light not only on the present needs of the unemployed young adults, their view on the parental support they receive, and the activities done by the young adults in exchange for the parental support, but also on the possible exchange of needs and support that will occur in the parent's old age. The present harmonious exchange is therefore viewed as a "good investment" for the future for both young adults and their parents. Studying other groups from different socio-economic classes, living arrangements, degree courses, lifestyles and between rural and urban settings would allow future researchers to broaden the knowledge of the exchange of needs and support between unemployed young adults and their parents.